E-Infrastuctures and E-Services for Developing Countries Second International ICST Conference, AFRICOM 2010, Cape Town, South Africa, November 25-26, 2010, Revised Selected Papers - Popescu-Zeletin, Radu.; Rai, Idris A.; Jonas, Karl.; Villafiorita, Adolfo; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the thoroughly refereed post-conference proceedings of the Second International ICST Conference on e-Infrastructure and e-Services for Developing Countries, AFRICOM 2010, held in Cape Town, South Africa, in November 2010. The 13 revised full papers presented were carefully reviewed and selected and cover a wide range of topics such as wireless network technologies, E-governance, as well as ICT for development and ICT business models and open-access.
Keywords: Computer science; Computer Communication Networks; Information systems; Education; Information Systems; Computer Science; Computers and Society; Computer Communication Networks; Computers and Education; Management of Computing and Information Systems; Computer Appl. in Administrative Data Processing; Personal Computing